Perlindungan Hukum terhadap Keamanan Data Nasabah Bank Mandiri dari Kejahatan Phishing - Fitria Wulandari; Dianne Eka Rusmawati; M. Wendy Trijaya; Maya Shafira; Dinda Anna Zatika (Lembaga Yasin AlSys, 2026)
Although the issue of personal data protection in the banking sector has received attention in various studies, studies that specifically examine the integration of the normative, ideal, and factual roles of banking in preventing phishing crimes remain limited. This study aims to analyze the role of Bank Mandiri in protecting customer data security from phishing crimes and to evaluate the effectiveness of legal protection based on laws and regulations in Indonesia. This study employed a qualitative approach with a case study design through a normative juridical method. Data were collected through library research and document analysis, and were then analyzed using descriptive-analytical techniques. The results show that Bank Mandiri has implemented comprehensive protection measures, including compliance with regulations, the use of advanced security technology, and customer education. In addition, the legal framework in Indonesia has provided preventive and repressive protection through various regulations governing data protection and cybercrime. These findings contribute to the development of legal protection theory and institutional responsibility in cybersecurity governance. This study concludes that synergy among banking institutions, regulators, and customers plays an important role in minimizing phishing risks. Therefore, improvements in cybersecurity infrastructure and the strengthening of digital literacy programs are needed to reinforce the protection of customer data. The implications of this study include theoretical contributions in the field of law and practical recommendations for strengthening data protection policies, while also opening opportunities for further studies on cross-sector collaboration and technological innovation in the financial sector.